2013
DOI: 10.1590/s0103-20032013000400009
|View full text |Cite
|
Sign up to set email alerts
|

Lar "Doce" Lar: uma análise do consumo de açúcar e de produtos relacionados no Brasil

Abstract: Resumo: O principal objetivo do presente trabalho é avaliar as características do consumo de açúcar e de produtos que usam açúcar em sua composição, utilizando dados das Pesquisas de Orçamentos Familiares (POF) de 2002/2003 e 2008/2009. Para tanto, foi utilizada a metodologia proposta por Hoffmann (1983, 2010) para a estimativa da elasticidade-renda. Os resultados mostram a significativa redução do consumo e dispêndio per capita associado ao açúcar cristal e refinado no período, bem como o aumento do consumo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The present results corroborate the percentage of the relative participation of food in the food purchases determined by Household Budget Surveys in the geographic regions of Brazil, which showed that the Northeast region has the highest percentage of sucrose consumption, while the South region has the lowest index (Brasil, 2009). Probably, the differences between regions are due to the family income, once the low price of refined sugar (sucrose) and the industrialised sugar‐sweetened products facilitates the consumption of sweetened foods by low‐income families, who are more prevalent in the North and Northeast regions of Brazil (De Souza et al ., 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results corroborate the percentage of the relative participation of food in the food purchases determined by Household Budget Surveys in the geographic regions of Brazil, which showed that the Northeast region has the highest percentage of sucrose consumption, while the South region has the lowest index (Brasil, 2009). Probably, the differences between regions are due to the family income, once the low price of refined sugar (sucrose) and the industrialised sugar‐sweetened products facilitates the consumption of sweetened foods by low‐income families, who are more prevalent in the North and Northeast regions of Brazil (De Souza et al ., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies on food consumption in Brazil (Brasil, 2009; De Souza et al ., 2013; Cavalcante et al ., 2017) have shown that the different income levels of the population in the regions have a great impact on the consumption of sugar and industrialised products containing sugar in its composition. In the Northeast region, in recent years, there has been an increase in the population income with a consequent increase in the consumption of food outside the home, leading to a reduction in the purchase of sugar, and a higher intake of industrialised products containing sugar (Cavalcante et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…According to the UN food balance sheet data, the New Zealanders, on average, consume about 147 g/day (37 teaspoons) of sugar [31]. Souza et al [32] showed that in 2002, 12.2 kg of granulated sugar and 6.1 kg of refined sugar per capita per year were consumed in Brazil. Considering a total of 18.3 kg and dividing this by 365 days corresponds to a consumption of 50.2 g of sugar per day [32], higher than the median values for the population of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Of this amount, US$ 10.90 million (nearly) correspond to sugar sales made by the mills used as raw material for industrialized products and retail sales of sugar in natura 3 . In this regard, Brazil is the world's largest producer and exporter of this product 4 . Sugar is used in a variety of foods, ranging from confectionery to flavoring in meats (hams, bacons, sausages and salamis).…”
Section: Introductionmentioning
confidence: 99%